PERTANGGUNGJAWABAN SOSIAL PABRIK ROKOK ALAINA DITINJAU DARI ETIKA BISNIS ISLAM - Kalimah, Siti (IAIN Tulungagung, 2015)
The background of this study because at Ngantruâs region there is one pesantrenâs, there is one effort which is Alainaâs Smoke Factory.Â Smoke Factory is one effort which of course it have good social impact that impacted big, be or little even but that it must each effort which walk and amends of course it performs to form social responsibility to surrounding society. The type of study is feld research using qualitative and desdriptive approach. The result of this studi is Alainaâs Smoke Factory make do corporate social responsibility, there are responsibility to God,Â responsibility to Nature and responsibility to other people. The type is sector religion, healthy sector and economi sector. Example to give work with recrutmen people and santri,Â faith job and other social job to welfare employee and peopleâs.Keywords: Social Responsibility, Islamic Business Ethic